Shift in the role of criminology in criminal law: Reflecting the doctrinal change - Md. Mahfuzur Rahman Khan; Rajia Sultana (Annals of Justice and Humanity, 2021)
Purpose: The study's aim is to assess how criminology's role in criminal law has changed over time. In addition, the author suggested that criminology can be used to test and suggest explanatory theories for criminal law rather than doctrinal shifts. Research methodology: The authors use literature-based observational analysis to assess how criminology's role in criminal law has evolved. Methodical investigation of logical literature uncovered the shift in the role of criminology in criminal law. Results: The authors claim that doctrinal changes have shifted perceptions of criminality, but the study's findings suggest otherwise. Doctrine changes mysteriously and without judicial acknowledgement, revealing shifting facts and suggests that the role of criminology in criminal law may be changing. Limitations: Even after a doctrinal shift, the authors argue, having criminological theories and perspectives helps assign proper rules to criminal law. Contribution: The study's findings support the often-criticized objectivist view of criminology but disagree on the subjectivist view of doctrine shifts. This study suggests that a new field will emerge that transcends both criminology and criminal laws rather than doctrine changes.